Evidence based training in cross-country skiing. Predicting the force generated by the skier - Ferreira, E. (University of Gothenburg, Department of Mathematical Sciences, 2019)
Evidence based training has been around for for while, where data is collected and pre-defined measures are used to evaluate the training session. Skisens AB are presenting new methods to evaluate a session which can be compared between sessions in a fair way, without having outside factors influencing the results by, measuring the force generated by the skier. Measuring the force generated involves customized handles that changes the dimensions of the handles and in the extension the ergonomics of the handles. This thesis aims to try to accurately predict the force generated in each stroke from the skier, in order for Skisens AB not having to measure the force using the customized handles. We propose an unsupervised detection algorithm, for detecting when a stroking motion is performed as well as a few model design for achieving the best predictive results.